Promising New Targets for the Treatment of Infections Caused by Acinetobacter baumannii: A Review - Malheiros Borges, Kellen Christina; Kipnis, André; Neves, Bruno Junior; Junqueira-Kipnis, Ana Paula (Current Drug Targets, 2024)
Acinetobacter baumannii is a globally disseminated Gram-negative bacterium that causes several types of serious nosocomial infections, the most worrisome being ventilator-associated pneumonia and bacteremia related to using venous catheters. Due to its great ability to form biofilms, combined with its survival for prolonged periods on abiotic surfaces and its potential to acquire and control the genes that determine antibiotic resistance, A. baumannii is at the top of the World Health Organization’s priority list of pathogens in urgent need of new therapies. In this sense, this review aimed to present and discuss new molecular targets present in A. baumannii with potential for promising treatment approaches. This review highlights crucial molecular targets, including cell division proteins, membrane synthesis enzymes, and biofilm-associated components, offering promising targets for novel antimicrobial drug development against A. baumannii infections.
Keywords: multidrug resistance